The Strategies of Refusing Requests By Students of Different Ethnic Groups - Arsen Nahum Pasaribu; Erika Sinambela; Tiara K Pasaribu; Jubil Ezer Sihite; Rony Arahta Sembiring (Syntax Corporation, 2021)
This study investigated the strategies used by students of different ethnic groups (Batak, Javanese, and Malay) in refusing requests. A total of 30 participants were involved in this research. Each ethnic group was represented by 10 students that came from three different universities in Medan, Indonesia. Discourse Completion Test (DCT) was used to collect the data. Data were analyzed by using refusal categorization. The results showed that the participants preferred to use indirect refusal strategies to respond to lecturer’s requests, and followed by direct and adjunct strategies respectively. This study also indicated that Batak students performed refusal acts more direct than any other Javanese or Malay students. Meanwhile Javanese students tend to employ refusals more indirect compared to any other students. The Malay students performed the acts moderately. The results indicated that the refusal strategies used by the students of three different cultural backgrounds might be influenced by their cultural circumstances. Future studies should be undertaken to investigate the phenomena in different research settings with more participants to be involved.